Analisis Pengeluaran Usaha Petani Nilam di Desa Warondo Kecamatan Sawerigadi Kabupaten Muna Barat - Nia, Murni; Abdullah Igo; Farni; Jumatin (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to analyze the income and expenses of patchouli farming businesses in Warondo Village, Sawerigadı District, West Muna Regency. Patchouli is a plantation commodity that has high economic value and has the potential to increase the income of rural communities. However, price fluctuations and high production costs are challenges that affect the income of patchouli farmers. The research method used is descriptive quantitative research. Data collection techniques were obtained through observation, interviews, and documentation of patchouli farmers who were respondents to the study. Data analysis was carried out by calculating the total production costs consisting of fixed costs and variable costs, total revenue, and income of patchouli farmers. In addition, the efficiency of the farming business was analyzed using the R/C ratio (Return Cost Ratio). The results of the study showed that patchouli farming in Warondo Village provided positive income for farmers. The total revenue obtained by farmers was greater than the total production costs incurred, so that patchouli farming was classified as profitable. The obtained R/C ratio indicates that patchouli farming is feasible to be developed and continued. Farmers' income is influenced by the size of production, land area, and management of production costs.